Formation of PbSe/CdSe Core/Shell Nanocrystals for Stable Near-Infrared High Photoluminescence Emission - Zhang, Yu (Springer, 2010)
PbSe/CdSe core/shell nanocrystals with quantum yield of 70% were obtained by the “successive ion layer adsorption and reaction” technology in solution. The thickness of the CdSe shell was exactly controlled. A series of spectral red shifts with the CdSe shell growth were observed, which was attributed to the combined effect of the surface polarization and the expansion of carriers’ wavefunctions. The stability of PbSe nanocrystals was tremendously improved with CdSe shells.